Meningkatkan Hasil Belajar Akidah Akhlak melalui Model Pembelajaran Komperatif Tipe Make A Match di SMA Islam Serambi Mekkah Meulaboh - Rosmanidar, Rosmanidar (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IAIN Lhokseumawe, 2023)
The aim of this study is to investigate the effectiveness of implementing the Make a Match cooperative learning model in enhancing the learning outcomes related to the topic of virtuous character in the subject of Akidah Akhlak (Faith and Morality) among 21 students in the 11th grade of Serambi Mekkah Islamic High School. The research subjects consisted of a total of 21 students from the school. The data analysis was conducted using the classical mastery approach. In the first cycle of the instructional intervention, which involved group-based learning, the level of classical mastery was observed to be 52.38%, with 11 out of 21 students achieving a satisfactory level of mastery. This outcome can be attributed to the students' hesitancy to ask questions, as evidenced by their behavior during the completion of the provided worksheets. Furthermore, the interaction among the students within the groups was primarily dominated by the more academically proficient students. Additionally, students exhibited a certain level of shyness when it came to presenting in front of the class, as indicated by their unpreparedness during group presentations. In the second cycle, a notable improvement in the level of classical mastery was observed, reaching 85.71%, with 18 out of 21 students demonstrating a satisfactory level of mastery. This improvement can be attributed to the enhanced student engagement and the commendable performance of both the students and the teachers during the implementation of the learning activities. In conclusion, this study provides empirical evidence that the implementation of the Make a Match cooperative learning model effectively enhances the learning outcomes pertaining to the subtopic of virtuous character among 11th-grade students at Serambi Mekkah Islamic High School.